PENGARUH RISIKO KREDIT DAN RISIKO LIKUIDITAS TERHADAP KINERJA KEUANGAN BANK YANG TERDAFTAR PADA BEI - Bimantara, Garin Pandu; Mariana, Mariana (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the impact of credit risk and liquidity risk on the financial performance of banks. The research sample consists of banks listed on the Indonesia Stock Exchange (IDX) that have completed their financial reports, provided data, published financial statements, and did not have negative ratios during the 2020-2022 period, using purposive sampling techniques. The research method used in this study is quantitative with a descriptive approach, where the data collection process is conducted through documentation and literature study methods, while the data analysis process is carried out using multiple linear regression tests and partial T-tests. The results show that credit risk is inversely related to the financial performance of banks, while liquidity risk is directly proportional to the financial performance of banks